Proposal of public policies regarding the reduction of deforestation in Romania - Nezalizov, Ana (Technium Social Sciences Journal, 2020)
Romania, the problem of deforestation is not a novelty, but, on the contrary, the Romanian state has been facing this for a long time, I would like to mention that the problem of deforestation is not only at national level, but is also felt globally. Massive deforestation is due to a high demand on the market, wood, but also wood products, the more they are illegal, because poaching is at high levels in our country. The issue of deforestation is not unique, but it still entails a lot of shortcomings, such as: desertification of the soil and decrease of its quality, which can be followed by water drying, landslides, etc., decreased air quality due to CO2 emissions, which is constantly increasing, floods, which endanger the citizens who have their homes nearby, thus biodiversity suffers, following the loss of shelter or climate change. The general objective of the public policy proposal is stopping illegalities regarding the forestry fund, improving air quality and biodiversity, stopping illegal trade.